Increased levels of ficolin-1 and of C3dg are independently associated with high risk of infection in patients with chronic kidney disease: a prospective cohort study - Sagedal, Solbjørg; Hovd, Markus; Åsberg, Anders; Mollnes, Tom Eirik; Klingenberg, Olav; Heldal, Torbjørn Fossum; Witczak, Bartlomiej J.; Hejlesen, Trine Korsgaard; Troldborg, Anne; Thiel, Steffen (Frontiers in Immunology, 2025)
Background and hypothesisInfection is a leading cause of morbidity and mortality in patients with chronic kidney disease (CKD). The complement system provides crucial first-line defense against pathogens. Mannose-binding lectin (MBL), ficolins (1, 2 and 3), and collectin-LK 1 (CL-LK) are pattern recognition molecules (PRMs) of the lectin pathway (LP) that recognize microbial surfaces and activate complement. C3dg is a complement cleavage fragment indicating complement activation. The aim of the study was to investigate whether levels of PRMs and C3dg are associated with the risk of significant infections requiring hospitalization in patients with CKD.MethodsThis prospective cohort study included 518 patients ≥18 years with CKD (eGFR<60 mL/min/1.73 m2), consecutively recruited between 2008-2022. About half (270/518) were in dialysis at inclusion. None of the patients were previously transplanted with any organ or stem cells. The primary endpoint was non-access-related infections requiring hospitalization. Patients were followed until kidney transplantation or death or until 31.12.2024. Plasma concentrations of the biomarkers were measured at inclusion. Time-to-event analyses using Cox regression were employed to assess associations with infection, adjusting for age, sex, diabetes, dialysis status, and dialysis vintage.ResultsDuring a median (interquartile range [IQR]) time of follow-up of 1.24 (0.49-2.76) years, 182 patients (35%) were hospitalized due to non-access infection. Higher baseline levels of ficolin-1 and C3dg were independently associated with infection risk, HR 3.05, 95% CI 1.25-7.43, p=0.01 and HR 2.97, 95% CI 1.37-6.44, p=0.006, respectively, for each log10 unit increase. In multivariable models including all biomarkers, only C3dg remained independently associated with infection (HR 2.81, 95% CI 1.23-6.43, p=0.01).ConclusionsHigh levels of complement activation (C3dg) and ficolin-1 were independently associated with increased infection risk in patients with CKD. A dysregulated complement activation rather than PRM deficiency seems to be a key pathogenic mechanism resulting in increased infection risk in advanced CKD.